The Role of Brand Reputation and Consumer Perception on Purchase Decisions for Buton Woven Fabrics - Bobi, Bobi; Wonua, Almansyah Rundu; Sudarnice, Sudarnice; Phradiansah, Phradiansah (PT. Sangadji Media Publishing, 2025)
Purpose – This study aims to investigate the impact of brand reputation and consumer perceptions on purchasing decisions for traditional woven fabrics from Buton. This study analyzes the influence of brand reputation and perception on purchasing decisions for woven fabrics in Mawasangka Tengah District, Central Buton Regency. Design/method/approach – This research utilizes an explanatory research model with a quantitative approach. The study employed survey methods, using a structured questionnaire to collect data from 100 respondents who had previously purchased Buton woven fabrics. The data were analyzed using Partial Least Squares (PLS) with SmartPLS 3.0 to assess the relationship between brand reputation, consumer perceptions, and purchasing decisions. Findings – The findings reveal that both brand reputation and consumer perceptions significantly influence purchasing decisions for Buton woven fabrics. Brand reputation has a positive and significant effect on purchasing decisions, as does consumer perception. These factors are crucial in shaping consumer behavior and guiding their decisions in the marketplace. Implications – This study contributes to the theoretical understanding of consumer behavior, particularly in the context of traditional products such as Buton woven fabrics. Practically, the findings can be used by local businesses and marketers to improve their branding and consumer engagement strategies to boost purchasing decisions. Novelty/Originality – The originality of this research lies in its focus on the traditional textile market in Buton, a region known for its unique woven fabrics. This study fills a gap in existing literature by exploring the relationship between brand reputation, consumer perception, and purchasing decisions in the context of local traditional products.